Three-dimensional true-FISP imaging of the coronary arteries: Improved contrast with T2-preparation - Shea, Steven M.; Deshpande, Vibhas S.; Chung, Yiu-Cho; Li, Debiao (Journal of magnetic resonance imaging, 2002)
Purpose To evaluate the effectiveness of a T2‐magnetization preparation scheme for improving coronary artery imaging with true fast imaging with steady‐state precession (True‐FISP). Materials and Methods Simulations were performed to compare the blood‐myocardium signal difference with no T2‐preparation to that with various T2‐preparation times (24, 40, and 60 msec) using an electrocardiogram (ECG)‐triggered, segmented True‐FISP acquisition. Seven volunteers were imaged to evaluate the effectiveness of T2‐preparation for coronary artery delineation using True‐ FISP and to optimize the T2‐preparation time. Results Simulations showed that T2‐preparation improved the signal difference between blood and myocardium over that without T2‐preparation. The optimal T2‐ preparation time was determined to be 40 msec. In volunteer studies, a T2‐ preparation time of 40 msec provided a significant improvement in contrast‐ to‐noise ratio (CNR) between the coronary arteries and myocardium over that without T2‐preparation. It also showed a significant improvement in visualizing the distal portions of the coronary arteries. Conclusion T2‐preparation improves coronary artery delineation with True‐FISP. J. Magn. Reson. Imaging 2002;15:597–602. © 2002 Wiley‐Liss, Inc.